Upaya Diplomasi Publik Dalam Mempromosikan Produk Fashion Indonesia di Luar Negeri - Aziza, Tiyya Nufikha; Purnawarman, Andi; Wicaksa, Arif (Interdependence Journal of International Studies, 2024)
Indonesia is one of the countries that has many kinds of cultures, which include dances, musical instruments, ritual traditions and clothing in each region in Indonesia. Public diplomacy is also seen based on a series of efforts to open good communication space and negotiate national elements in the international world. To get the attention of the international community and give a good image to Indonesia, it is necessary to make efforts made by Indonesia, namely by promoting fashion to the international community in order to achieve Indonesia's national interests. Although it is undeniable, a number of fashion product brands in Indonesia still need improvement to compete with foreign brands, because there are still many people who think that the quality of foreign brands is better, but with the creativity of Indonesian designers who are starting to provide ready-to-wear product choices at affordable prices than foreign brands. Human resources and a lot of international markets will have potential in the fashion sector so that special attention is shown by the government. Not only the government but citizens also have the ability to be actors in diplomacy. This study aims to determine public diplomacy efforts in promoting Indonesian fashion products abroad. This research is descriptive research. The data used in this study are secondary data sourced from articles, online journals, books, and internet facilities. This research uses library research data collection techniques and the data analysis technique used is qualitative data analysis technique. This research uses the theoretical framework of public diplomacy and creative industries. The results showed that public diplomacy efforts in promoting Indonesian fashion products abroad are by collaborating between the government and the private sector, as well as facilitating and promoting domestic products to the international world.